Trypanocidal effect of Diminazene aceturate by intranasal administration: Comparison among formulations - Fuchs, Alicia Graciela (2021)
The standard treatment for nagana and surra, vector–born parasite diseases, is a single intramuscular (i.m.) dose of diminazene aceturate (DA), an aromatic diamidine. Due to discontinuity of public provision of veteri-nary services or to lack of access to remote areas, low income farmers inject livestock and other domestic animals by themselves. We tested a not explored administration route for drugs against parasitological infections: the intranasal one. DA dissolved in water did not reach an effective drug concentration. Methods: Mice were infected with Trypa-nosoma brucei brucei or Trypanosoma evansi and treated with different formulations of DA. Survival, parasitemia, body weight and behavior were recorded. Results: DA formulated with chitosan reached a lethal concentration for bloodstream parasites. Residual parasites were absent, as demonstrated by immunosuppression. Conclusion: The intranasal route is an effective, safer, and easier way to perform antiparasitic treatments in animals.